A IMPLEMENTASI PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MINAT BELAJAR PAI DI SMPN 2 NGORO JOMBANG: IMPLEMENTASI PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MINAT BELAJAR PAI DI SMPN 2 NGORO JOMBANG - Chafid Charis, Mochammad; Anshori, Sholihul (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
Abstract: A situation that seeks to create a learning environment between students that can be active with each other to show that they are able to go through the learning process with the teacher by expressing opinions to each other is called the implementation of an interactive learning model. Based on the problems above, this study has 3 related objectives, namely how to implement interactive learning, learning interest and supporting factors as well as obstacles to implementing interactive learning at SMPN 2 Ngoro Jombang. The type of research is case study research. The model taken as a method is qualitative. Based on the results of the study it was found that: this interactive learning can make students more easily conditioned because of the deep attention that is carried out by the teacher because there is two-way communication, and this student learning interest can occur because there are fun methods for students and there are adequate facilities for doing so. activities that lead to students who are able to learn actively and feel happy in participating.